Structural evolution of small gold clusters doped by one and two boron atoms. Issue 32 (3rd October 2014) - Grande‐Aztatzi, Rafael; Martínez‐Alanis, Paulina R.; Cabellos, José Luis; Osorio, Edison; Martínez, Ana; Merino, Gabriel
<x xml:space="preserve">Abstract</x> The potential energy surfaces (PES) of a series of gold–boron clusters with formula AunB (n = 1–8) and AumB2 (m = 1–7) have been explored using a modified stochastic search algorithm. Despite the complexity of the PES of these clusters, there are well‐defined growth patterns. The bonding of these clusters is analyzed using the adaptive natural density partitioning and the natural bonding orbital analyses. Reactivity is studied in terms of the molecular electrostatic potential. © 2014 Wiley Periodicals, Inc.